142 FRAILTY IDENTIFICATION AND INTERDISCIPLINARY ASSESSMENT OF OLDER PEOPLE IN THE EMERGENCY DEPARTMENT. (18th November 2021) - Edge, L; Cunningham, C; Murphy, N; Dillon, A; Flynn, S; O'Shaughnessy, Í; Davis, A; O'Rourke, B; Brossier, L; Doran, C; Hennessy, A; Kennedy, U; et al.
Abstract: Background: Older People are attending Emergency Departments (EDs) in increasing numbers but the optimal assessment measures to use have yet to be established. This study examined the clinical utility of different assessments of strength, functional mobility, sarcopenia, cognition and frailty used by the physiotherapist in an interdisciplinary team (IDT) in the ED and determined any associations with clinical outcomes. Methods: This observational cross-sectional study recruited adults ≥70 years who were assessed by an IDT on weekdays during working hours. Demographic variables such as age, gender, social situation, baseline mobility, falls and clinical measures such as Clinical Frailty Scale (CFS), 4AT, hand-held dynamometry, calf circumference and functional mobility in ED were recorded. Clinical outcomes were admission to hospital, discharge from ED with onward referral (ambulatory care or community) and discharge from ED with no referral. Ethical approval was obtained and SPSS was used for statistical analysis. Results: Two hundred and fifty four participants were recruited, 58.3% female, mean age 80.23 (SD 6.56). Median CFS was 4 (IRQ 2.0), range 1–7 with 32.7% (n = 83) considered frail. Sarcopenia prevalence was 89.3% using grip strength and 7.1% using calf circumference. Grip strength predicted frailty even after adjusting for age (p < 0.0001), gender (p < 0.0001) and falls (p = 0.043). Admission to hospital was predicted by major diagnostic category (p = 0.016) and inability to sit to stand independently in ED (p < 0.0001). Seventy percent (n = 179) of participants were discharged from ED, with 27.6% referred to ambulatory care or community services. Onward referral was predicted by frailty (p = 0.016) and falls in the last six months (p = 0.028). Conclusion: Grip strength in addition to a validated tool such as CFS may assist an experienced IDT in identifying frailty, which can in turn inform decision-making regarding ED disposition and pathways of care for older people. Functional assessment in the ED is also important to determine the need for hospital admission.